TUJUAN NEGARA DALAM ISLAM MENURUT YUSUF AL-QARADHAWI - Sigit Ridwan Abdullah (Faculty of Sharia and Law, Sunan Gunung Djati Islamic State University of Bandung, 2017)
AbstractYusuf al-Qaradawi is one of the figures of so many scholars who contributed to the thinking of the Islamic state. His attention to politics and state is evidenced by the presence of some of his works such as الإسلام في الدولة فقه من (Fiqh of State in Islamic Perspective), الشرعية السياسة (Political Sharia), الإسلام مواجهة في العلماني التطرف (Extreme Secular Attitudes towards Islam), وهم لا حقيقة اللإسلامية اللأمة (The Political Unit of Ummah is a Reality). This research tried to review Yusuf al-Qaradawi's view on Islamic state, using descriptive analytical methods and literature review upon the above stated Yusuf al-Qaradawi's books or writings. The research result shows that Islamic state according to Yusuf al-Qaradawi is